Resource testing of modified plain bearings for the aviation industry - Khimko, M.; Khimko, A.; Mnatsakanov, R.; Mikosianchyk, O. (Problems of Tribology, 2024)
The resource tests of plain bearings with metal-polymer tribo-systems developed for the aviation industry are presented. The purpose of the work is to determine the wear resistance of modern anti-friction polymer materials in plain bearings in comparison with metal fluoroplastic tape. The uniqueness of the tests lies in the use of a combination of high-performance polymer materials in a pair with chromium and molybdenum coating during the reversible movements of plain bearings. Since the use of such bearings is mass in nature, the use of titanium materials in the manufacture of bearing cages will allow to significantly reduce the weight of the aircraft and increase its efficiency. It was determined that a plain bearing with a polymer material of carbon and polyamide fibers and PTFE with functional additives shows a wear resistance 1.8-2 times greater on the segment of 40-100 thousand cycles than bearings with other materials during laboratory resource tests. Also, industrial tests have established that after 2 million cycles, a hinged bearing with a metal-polymer tape shows a result that is 1.2-1.5 times lower in wear resistance than polymer materials, but all these results are within the tolerances of normal bearing operation. Industrial tests have proven that at replacing the inner ring of a plain sliding bearing with a titanium alloy with a molybdenum coating, the wear resistance is almost the same or slightly lower than when the polymer rubs against steel. Technological recommendations have been developed and a new design and materials of plain sliding bearings with polymer anti-friction coatings for the aviation industry have been proposed. The implementation of technological recommendations in the production of bearings will allow to move away from the universality of the use of plain bearings and extend their wear resistance and durability in general due to the use of the full thickness of the polymer material and the development of bearings with predicted characteristics for a specific task.